Effects of probiotic intervention on obesity-related miRNAs - Okuka, Nina; Hippe, Berit; Djordjević, Brižita; Ivanović, Nevena (Archives of Pharmacy, 2024)
Obesity is considered to be a chronic complex disease that increases the risk of diabetes, heart diseases and certain cancers. According to the literature, in obese people the gastrointestinal microbiota is disturbed, which could be the cause of the onset of obesity and related diseases. Moreover, there are small non-coding RNAs (microRNAs) that are disturbed in obesity, which are also considered to be a possible mechanism of probiotics’ action. Certain microRNAs are involved in the development and metabolism of adipose tissue cells, as well as the secretion and action of insulin, showing that changed expression of certain miRNAs could have a significant impact on the onset and development of obesity and obesity-related diseases. Thus, miRNAs are considered to be possible markers for the diagnosis and prognosis of various metabolic diseases, and possible therapeutic targets for the treatment of obesity and related diseases. Considering the growing need of the healthcare system for nutraceuticals and dietary supplements that present effective and safe medical nutritive therapy in obese individuals, this work aimed to assess the beneficial effects of probiotics on obesity-related microRNAs. In this review, we described the role of microRNAs and probiotics in obesity and the association between probiotics and obesity-related microRNAs. Circulating miRNAs’ profile in obese individuals significantly differs from that of normal-weight individuals. miRNAs such as miR-155, miR-221, miR-24-3p, and miR-181a are over-expressed, while miR-26b and 125a are under-expressed in obese patients compared to non-obese individuals. It has been found that supplementation with Bifidobacterium bifidum and Lactobacillus acidophilus could downregulate the expression of miR-155 and miR-221, and upregulate the expression of miR-26b. Supplementation with a probiotic formulation containing S. boulardii, L. plantarum 299v, and octacosanol led to the downregulation of miR-155 and miR-24-3p expression. miR-125a and miR-181a were upregulated and downregulated, respectively, after the intervention with L. delbrueckii and L. rhamnosus. After reviewing the available literature, we can conclude that probiotics have beneficial effects on microRNAs altered in obesity, which could provide an effective strategy for the management of obesity.
Keywords: obesity; microRNA; probiotics